Environmental Noise Pollution: Developing an Effective Public Health Response (International Journal of Food and Nutritional Sciences, 2022)
Unwanted sound is referred to as noise. All undesirable sounds in our communities, save those that originate in workplaces, are classified as environmental noise. Noise pollution, which is a type of air pollution, is hazardous to one's health and well-being. It will also continue to expand as motorway, rail, including air traffic continue to grow, all of which are major examples of environmental noise. Noise pollution has a wide range of potential health impacts that are widespread, long-lasting, and professionally and socially significant. Noise has immediate and cumulative negative health consequences, as well as degraded household, social, professional, and learning environments, resulting in tangible and intangible costs. It disrupts sleep, concentration, communication, and recreational activities. The goal of intelligent government restrictions should be to safeguard citizens from the harmful impacts of airborne pollution, especially noise pollution. People should be able to choose another nature of personal acoustical environments rather than imposing rules on them by others.